Codes - "Nelson, Nigel" (Wayland Hove, 1993)
The book Codes (Communications) by Nigel Nelson, illustrated by Tony De Saulles, published in 1994 by Wayland. This book is part of the "Communications" series and explores the various ways in which signs and symbols are used to convey information.